Estimating the Pen Trajectories of Static Handwritten Scripts using Hidden Markov Models - Nel, Emli-Mari (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Electrical and Electronic engineering))--University of Stellenbosch, 2005.